Reducing unemployment through fundamental labour market reform - Dennis J. Snower (Anglo-German Foundation for the Study of Industrial Society, 2006)
Professor Dennis J. Snower, President of the Kiel Institute for the World Economy since 2004, addresses the riddle of persistent unemployment in free market economies, outlining first a set of popular explanations for this phenomenon (and quickly showing why they are inadequate), then the main explanatory theories put forward by academic economists. He goes on to draw conclusions from the common ground shared by those theories regarding the fundamentals of effective labour market policy, and proposes on that basis two innovative measures which would address the underlying problems: benefit transfer programmes and unemployment accounts. He concludes by assessing the wider economic implications of introducing these measures.
Keywords: 330; Arbeitsmarktpolitik; Voucher; Vermögensbildung